Absorption and Bio-Transformation of Selenium Nanoparticles by Wheat Seedlings (Triticum aestivum L.) - Hu, Ting; Li, Huafen; Li, Jixiang; Zhao, Guishen; Wu, Wenliang; Liu, Liping; Wang, Qi; Guo, Yanbin (Frontiers in Plant Science, 2018)
Elemental selenium is one of the dominant selenium species in soil, but the mechanism of its uptake by plants is still unclear. In this study, nanoparticles of elemental selenium (SeNPs) with different sizes were prepared, and their uptake and transformation in wheat (Triticum aestivum L.) were analyzed in hydroponic experiments by HPLC-ICP-MS. We found that the SeNPs can be absorbed by wheat seedlings, and the process is energy independent. The addition of aquaporins inhibitor caused 92.5% and 93.4% inhibition of chemosynthesized SeNPs (CheSeNPs) and biosynthesized SeNPs (BioSeNPs) absorption by wheat roots, respectively. The 40 nm SeNPs uptake by wheat roots was 1.8-fold and 2.2-fold higher than that of 140 nm and 240 nm, respectively. The rate of SeNPs uptake in wheat was much slower than that of selenite (Se (IV)), and CheSeNPs were more efficiently absorbed than BioSeNPs. The SeNPs were rapidly oxidized to Se (IV) and converted to organic forms (selenocystine (SeCys2), se-methyl-selenocysteine (MeSeCys), and selenomethionine (SeMet)) after they were absorbed by wheat roots. Additionally, we demonstrated that the aquaporin function in some way is related to the absorption of SeNPs. The particle size and synthesis method of the SeNPs affected their uptake rates by plants. Taken together, our results provide a deep understanding of the SeNPs uptake mechanism in plants.